Factors influencing intention to install solar photovoltaic among households in the Klang Valley, Malaysia - Sharifuddin, Nur Shazleen Ilyana (2021)
For decades, Malaysia depend heavily on fossil fuels as the main energy sources to generate energy. To decrease dependency on fossil fuels sources and support Sustainable Development Goal (SDG) 7, Malaysia has implemented several renewable energy program, particularly solar program. The newest solar program introduced was Net Energy Metering (NEM) program, a revised program from previous progam which was Feed-in Tariff (FiT) program. Even though many aspect have been improved in NEM program, the adoption rate for solar PV among households still remains low. Thus, this study was necessary to examine various factors that are assumed to influence the intention of households in the Klang Valley to install solar PV. The Theory of Planned Behaviour has been extended by adding perceived cost as new variable in an attempt to identify behavioural intention towards the installation of solar PV in Klang Valley. This study empirically aims to examine how attitude, subjective norm, perceived behavioural control and perceived cost contribute to the behavioural intention of using solar PV in Klang Valley, Malaysia. A total of 500 questionnaires have been distributed at 5 selected local authority areas in Klang Valley using disproportionate stratified random sampling. A 410 responses were analysed using Partial Least Square Structural Equation Modelling (PLS-SEM). The findings of this study showed that attitude, subjective norm, perceived behavioural control and perceived cost have a significant influence on intention to install solar PV. Besides, the result demonstrated that subjective norm and perceived cost are positively mediated by attitude in influencing intention to install solar PV. The findings have contributed towards the advancement of knowledge in the field of solar PV under Net Energy Metering (NEM) programme. Besides, thesefindings also are useful for policy makers and solar PV marketers to strategize their plan to increase households adoption rate of solar PV in Malaysia.